Perancangan Interior Terminal Kedatangan Syamsudin Noor Airport Banjarmasin Dengan Pendekatan Sustainable Design - Astrelia Nia Derriani; Yusita Kusumarini; Jean Francois Poilot (Intra, 2016)
have been increasing lately, the local government continues to balance the growth with improving the quality of existing infrastructure in the city of Banjarmasin. One of its main targets is Syamsudin Noor Airport, where the government plans to create a new terminal at the international scale. As the starting gate to the city of Banjarmasin, the airport is considered to be a top priority that must be improved in quality and quantity in order to support the economic growth rate in the city of Banjarmasin. Seeing the opportunity is exactly what makes an airport Syamsudin Noor as an object on the design this time. Along side with the planning process that has been entered into the bidding process, then some technical matters to the concept has been determined. So it developed into three main purpose of designing this time, where the arrival terminal at the airport Syamsudin Noor will be able to describe the characteristic of Banjarmasin city, accompanied by a Sustainable Design as an embodiment of the concept of a global concept that has been determined to be ecological, as well as the design of the arrival terminal capable enough to adapt the shape of technical and architectural terms. This goal is accomplished by designing a method adapted from the Design Thinking process undertaken by Sun Sigma Framework for New Product. From the results of the design process can be seen that the achievement of the first goal is reached by election of the material with local materials, notching obtained from processed philosophical form of local buildings, and involving the local community. For the second purpose was reached with universal design, selection of materials and environmentally friendly interior elements that support energy efficiency. As well as on the third objective embodied in the arrangement of the layout, as well as the circulation of the user who adheres to the technical and architectural